Corporate Cash Holding Behavior and Financial Environment: A Critical Review - Tahir, Muhammad Sohail; Alifiah, Mohammad Norfian (International Journal of Economics and Financial Issues, 2015)
Research on corporate liquidity management practices has mainly focused on the trade-off between the potential costs and benefits of holding cash. However, in order to improve the firm financial performance, much remained to be understood, particularly, the cash holding behavior of firms. Furthermore, this study reveals that contemporary literature in the area of cash management may overlook the industry and institutional context of firms at sector level. In addition, sectors are important to study due to their unique characteristics and heterogeneity in the financial environment. Therefore, in order to improve the firm’s financial performance, future studies in developing markets can be focused on the potential impact of different financial environment, particularly, the significance of capital structure and dividend policies on corporate cash holding mechanism at sector level. Keywords: Financial Performance; Capital Structure; Dividend Policy; Cash Holding JEL Classifications: N2